Returns to Investment in Education : A Further Update - Psacharopoulos, George (World Bank, Washington, DC, 2014)
Returns to investment in education based on human capital theory have been estimated since the late 1950s. In the 40-plus year history of estimates of returns to investment in education, there have been several reviews of the empirical results in attempts to establish patterns. Many more estimates from a wide variety of countries, including over time evidence, and estimates based on new econometric techniques, reaffirm the importance of human capital theory. The suthors review and present the latest estimates and patterns as found in the literature at the turn of the century. However, because the availability of rate of return estimates has grown exponentially, the authors include a new section on the need for selectivity in comparing returns to investment in education and establishing related patterns.